La mensualización de los décimos tercer y cuarto sueldo en el Ecuador y su incidencia en el consumo de los hogares, del cantón Quevedo, periodo 2014-2015 - Loyo Rosado, Bianca Suleika (2016)
This research on "The Monthly Wages tenths third and fourth salary in Ecuador and its impact on household consumption, the Quevedo canton period, 2014-2015" aims to study qualitatively the effect on society on government reforms through executive power according to the Ministry of Labor Relations, on the Monthly wages tenths third and fourth wages, which the employee is dissatisfied with such provisions, besides being more public sector. The research is based on the variables of research on the Monthly Wages tenths third and fourth salary, work environment, consumption of households, income level, determinants of savings, which were provided through texts, magazines and scientific articles, also should be considered that the research methodology consists of field research, descriptive, with their deductive and inductive methods, pursued by the techniques, tools and research design. In conclusion Monthly Wages tenths third and fourth salary influences with a percentage of 34% on a regular basis has a positive impact on public and private companies in the canton Quevedo, unlike those in the private sector they remain with their say in cumulatively, but in the public sector they are unhappy because they cannot meet their economic needs reducing their income. It is recommended that persons employed in private enterprises have the option to choose whether to receive their say third or fourth salary with Monthly Wages or accumulated, it is recommended to take the best decisions while maintaining the responsibility of managing in the best way their economic resources, can contribute to the family consumption and maintaining a culture of savings.